Dual physiological responsive structural color hydrogel particles for wound repair - Li Wang; Lu Fan; Anne M. Filppula; Yu Wang; Feika Bian; Luoran Shang; Hongbo Zhang (Bioactive Materials)
Hydrogel-based patches have demonstrated their values in diabetic wounds repair, particularly those intelligent dressings with continuous repair promoting and monitoring capabilities. Here, we propose a type of dual physiological responsive structural color particles for wound repair. The particles are composed of a hyaluronic acid methacryloyl (HAMA)-sodium alginate (Alg) inverse opal scaffold, filled with oxidized dextran (ODex)/quaternized chitosan (QCS) hydrogel. The photo-polymerized HAMA and ionically cross-linked Ca-Alg constitute to the dual-network hydrogel with stable structural color. Furthermore, the ODex/QCS hydrogel, combined with glucose oxidase (GOX), exhibits pH/glucose dual responsiveness. Moreover, antimmicrobial peptide (AMP) plus vascular endothelial growth factor (VEGF) are comprised within the GOX-doped ODex/QCS hydrogel. In the high-glucose wound environment, GOX catalyzes glucose to generate acidic products, triggering rapid release of AMP and VEGF. Importantly, this process also leads to structural color changes of the particles, offering significant potential for wound monitoring. It has been demonstrated that such particles greatly promote the healing progress of diabetic wound in vivo. These results indicate that the present dual responsive particles would find valuable applications in diabetic wounds repair and the associated areas.